Development and performance evaluation of a solar dryer of copra - SAI KRISHNA, V; Er. George Mathew (Guide) (Tavanur Kelappaji College of Agricultural Engineering and Technology)
Development and performance evaluation of a solar dryer of copra
Development and performance evaluation of a solar dryer of copra